Preparing prospective primary school teachers in teaching informal statistical inference - Blomberg, Per (NOMAD Nordic Studies in Mathematics Education, 2025)
In recent decades, the statistics education community has focused extensively on research aimed at modernising mathematics curricula by integrating powerful statistical concepts relevant to the 21st century. As a result, the professional development needs of statistics teachers are evolving. There is an increasing demand for teachers to be well-equipped to teach foundational statistical concepts, including inferential statistics, and gaining these insights has become essential. This paper presents findings from an educational design research study conducted with participants in primary teacher education. The study outlines a design principle with three sub-components, intended to guide teacher training in statistical inference. The conclusion highlights the importance of statistical inference as a central theme in statistics education, with significant implications for school statistics and curriculum evaluation.